Impact of government expenditure on economic growth in Nigeria, 1970-2019 - Chandana Aluthge; Adamu Jibir; Musa Abdu (CBN Journal of Applied Statistics, 2021)
This study investigates the impact of Nigerian government expenditure (disaggregated into capital and recurrent) on economic growth using time series data for the period 1970-2019. The paper employs Autoregressive Distributed Lag (ARDL) model. To ensure robustness of results, the study accounts for structural breaks in the unit root test and the co-integration analysis. The key findings of the study are that capital expenditure has positive and significant impact on economic growth both in the short run and long run while recurrent expenditure does not have significant impact on economic growth both in the short run and long run. The study recommends that government should increase the share of the capital expenditure especially on meaningful projects that have direct bearing on the citizen's welfare. Government should also improve the spending patterns of recurrent expenditure through careful reallocation of resources toward productive activities that would enhance human development in the country.
Keywords: C32; H54; H50; O40; O41; 330; ARDL; capital expenditure; endogenous growth model; economic growth; recurrent expenditure